PATRIOTISME TOKOH DEWI AYU DALAM NOVEL CANTIK ITU LUKA KARYA EKA KURNIAWAN - Anisa Choir (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2021)
This article scrutinizes the patriotism side of the character Dewi Ayu in the novel entitled Cantik Itu Luka by Eka Kurniawan. As a prostitute at Halimunda, Dewi Ayu has an ambiguous nature. She has a tremendous patriotic character, although her profession broke the social norms. This study aims to expose the patriotism of Dewi Ayu in Eka Kurniawan's Cantik Itu Luka. The methodology used in this study is a qualitative methodology approach and a content analysis method by describing the behaviour of Dewi Ayu based on events in the narrative texts. Based on data processing, the study results show Dewi Ayu's patriotism, such as her strict, self-sacrificing, responsible, and a sense of sympathy for indigenous women.